Monitoramento de poluentes atmosféricos em aeroportos: a qualidade do ar no Aeroporto Bacacheri - Jabonski, Carlos Daniel (2017)
Aviation, from early days to the present, arouses great curiosity. The flight, the ease in shortening distances, uniting people, cities and countries are factors of great enthusiasm. Air traffic is growing, it is just j observe the daily routine at an airport. However, actions such as triggering, taxiing, taking off and landing aircrafts generate emissions of air pollutants. This research consisted of monitoring: ozone gases (O3), sulfur dioxide (SO2), nitrogen monoxide (NO), nitrogen dioxide (NO2) and carbon monoxide (CO), at Bacacheri Airport in Curitiba, with a portable station for atmospheric pollutants monitoring, model AQMesh. The monitoring station was installed at different periods in the aircraft maneuvering yard and hangars 12 and 34 which belong to the Military Police Battalion of Air Operations of Paraná, in the months of June, July and October of 2016, totaling forty-four days of measurements. The Air Quality Index Bulletin of the Bacacheri Airport was elaborated, and the results the air pollutants monitoration at the airport were compared with data from the monitoring stations located in the neighborhood Santa Cândida and Ouvidor Pardinho square in Curitiba. From these analyzes, it was observed that only at the airport, sulfur dioxide changed the air quality index by classifying it as regular. For the data interpretation, the Principal Component Analysis was also applied aiming at identifying similarity between the variables. The air pollutant monitoring station was an effective tool to carry out this study, which presents information for future studies and for a possible atmospheric emissions management program at airports.